The potential of viruses to influence the magnitude of greenhouse gas emissions in an inland wetland. (1st April 2021) - Bonetti, Giuditta; Trevathan-Tackett, Stacey M.; Carnell, Paul E.; Macreadie, Peter I.
Highlights: Investigation on virus-host interactions during a wetland hydrological restoration Viral life strategy switched after the introduction of water Correlation between the carbon released by the viral lysis and total carbon emissions Viral life strategies potentially contribute to the regulation of greenhouse gas emissions Graphical abstract: Image, graphical abstract Abstract: Wetlands are among the earth's most efficient ecosystems for carbon sequestration, but can also emit potent greenhouse gases (GHGs) depending on how they are managed. Global management strategies have sought to maximize carbon drawdown by wetlands by manipulating wetland hydrology to inhibit bacterially-mediated emissions. However, it has recently been hypothesized within wetlands that viruses have the potential to dictate the magnitude and direction of GHG emissions by attacking prokaryotes involved in the carbon cycle. Here we tested this hypothesis in a whole-ecosystem manipulation by hydrologically-restoring a degraded wetland ('rewetting') and investigated the changes in GHG emissions, prokaryotes, viruses, and virus-host interactions. We found that hydrological restoration significantly increased prokaryotic diversity, methanogenic Methanomicrobia, as well as putative iron/sulfate-cyclers (Geobacteraceae), nitrogen-cyclers (Nitrosomonadaceae), and fermentative bacteria (Koribacteraceae). These results provide insights into successional microbial community shifts during rehabilitation. Additionally, in response to watering, viral-induced prokaryotic mortality declined by 77%, resulting in limited carbon released by viral shunt that was significantly correlated with the 2.8-fold reduction in wetland carbon emissions. Our findings highlight, for the first time, the potential implications of viral infections in soil prokaryotes on wetland greenhouse gas dynamics and confirm the importance of wetland rehabilitation as a tool to offset carbon emissions.